The Livelihood Impacts of Cash Transfers in Sub-Saharan Africa: Beneficiary Perspectives from Six Countries. (November 2017) - Fisher, Eleanor; Attah, Ramlatu; Barca, Valentina; O'Brien, Clare; Brook, Simon; Holland, Jeremy; Kardan, Andrew; Pavanello, Sara; Pozarny, Pamela
Highlights: Social protection can strengthen beneficiaries' strategic livelihood choices. Cash transfers must be regular and predictable to facilitate livelihood improvement. Cash transfers are not uniformly effective at increasing productive investment. Large welfare and education needs can constrain cash transfers' productive use. Economic collaboration and risk sharing can be enhanced. Summary: Cash transfers (CTs) are a social protection mechanism to reduce the poorest households' vulnerability to shocks and build human capital by smoothing consumption and sustaining expenditure on education and social welfare. Our study examines whether and how CTs go beyond welfare objectives to promote livelihoods. Presenting a cross-case analysis using original qualitative data on beneficiary perspectives from six African countries—Kenya, Ethiopia, Malawi, Lesotho, Zimbabwe and Ghana—we explore CT livelihood impacts within household economies and social networks, paying attention to gender issues. We find that a small but predictable flow of cash improves strategic livelihood choices and stimulates productive investments, including through positive effects on beneficiary entry into risk-sharing arrangements and networks for economic collaboration. Levels of household vulnerability and labor constraint nevertheless significantly mediate the ability of CTs to consolidate livelihood outcomes. The varying availability of economic opportunities, plus effective program implementation, also shape livelihood impact. Incorporating beneficiary perspectives brings to the fore the multi-dimensionality of CT effects on experiences of poverty and deprivation, including gender dynamics and intangibles such as dignity and respect; they add powerful realism to the influence of the CT on both immediate survival and livelihood choices. Beyond this, they confirm wider knowledge on productive impact and bring nuance to the conditions under which, and mechanisms by which beneficiaries' use CTs to build productive capability and assets and to make strategic livelihood choices.